2021
DOI: 10.1111/dth.14823
|View full text |Cite
|
Sign up to set email alerts
|

Mask‐induced Koebner phenomenon and its clinical phenotypes: A multicenter, real‐life study focusing on 873 dermatological consultations during COVID‐19 pandemics

Abstract: During COVID-19 pandemic, wearing masks for prevention became mandatory but evidence suggest that is also detrimental for skin. Although facial dermatoses due to masks increase in both healthcare workers and general population, a pathogenetic hypothesis remains still elusive. We aimed to evaluate the prevalence of dermatological consultations due to Koebner triggered dermatoses In this prospective, multicenter, real life study carried out in Italy from March 11th to December 11th 2020 during COVID-19 pandemics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…During the COVID-19 pandemic, the use of medical devices (i.e., masks) has become a mandatory preventive strategy but mask choice is of paramount importance in patients with pre-existent facial dermatoses and especially in MCS patients [ 117 , 118 , 119 ]. Thus, the experts agreed to suggest this kit of medical devices for MCS patients according to their clinical profile to prevent daily flares: Masks (latex-free paper face masks or cotton masks and filters and/or masks with a high-efficiency particulate absorbing filter (HEPA) and activated carbon filters).…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID-19 pandemic, the use of medical devices (i.e., masks) has become a mandatory preventive strategy but mask choice is of paramount importance in patients with pre-existent facial dermatoses and especially in MCS patients [ 117 , 118 , 119 ]. Thus, the experts agreed to suggest this kit of medical devices for MCS patients according to their clinical profile to prevent daily flares: Masks (latex-free paper face masks or cotton masks and filters and/or masks with a high-efficiency particulate absorbing filter (HEPA) and activated carbon filters).…”
Section: Resultsmentioning
confidence: 99%
“…39 Effective risk communication represents the cornerstone for a risk management strategy aiming to improve not only how people perceive health risks during the pandemic but also how they react to healthcare emergencies and adhere to self-protective measures. 11,[40][41][42] In the case of the COVID-19 pandemic, with its associated high transmission rates, morbidities, and mortality, lack of proper risk communication can exaggerate panic displays, increase public confusion, or lead to unfavorable perception towards the benefits of preventive measures. 43 In this regard, HCWs are the frontline soldiers in the fight against COVID-19; previous reports demonstrated that HCWs account for up to 24% of the global number of documented COVID-19 cases.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, healthcare systems had to face a complete reset, [1][2][3][4] both healthcare workers and patients had to perform several preventive strategies, such as donning masks 5 that have high social 6 and medical costs. 7,8 In this scenario, traditional coffee vendors in Ethiopia had to operate and design a completely new vendor-buyer interaction, but its rebound on mental health was not previously evaluated. COVID-19 itself and the health-related measures being taken to mitigate the transmission of the virus has also resulted in a profound physical, social, economic and psychological crisis since its outbreak.…”
Section: Introductionmentioning
confidence: 99%